Peningkatan Pertumbuhan dan Produksi Jagung Manis Melalui Penerapan Sistem Pengolahan Tanah dan Pemberian Mulsa pada Lahan - Gribaldi Gribaldi (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2016)
Gribaldi et al, 2016.  Increasing of Growth and Sweet Corn Production Through Implementationof Tillage System and Mulching on The Dry Land. JLSO 5(2):119-126. Tillage and mulching are intended to create good soil conditions which is suitable for plant growth so could increase crop production. This study aims to gain tillage system and the organic mulching which  can improve the growth and the production of sweet corn on the dry land.  The experimental design used in this study is a randomized block design arranged as factorial with two treatments factors and three replications. The first factor is tillage (P), which consists of no tillage (P0), minimum tillage (P1), and maximum tillage (P2). The second factor is mulching (M), which consists of no mulching (M0), mulching (M1). The results showed that  tillage systems affect the growth and production of sweet corn,  mulching no effect on the growth and production of sweet corn, and mulching on minimum tillage tend to affect both the growth and the production of sweet corn on dry land.